Comparison of ultrasound‐guided peripheral intravenous catheter insertion with landmark technique in paediatric patients: A systematic review and meta‐analysis. (20th April 2022) - Kleidon, Tricia M; Schults, Jessica; Paterson, Rebecca; Rickard, Claire M; Ullman, Amanda J
Abstract : Background: Paediatric peripheral intravenous catheter (PIVC) insertion using traditional landmark insertion technique can be difficult. Aim: To systematically review the evidence comparing landmark to ultrasound guidance for PIVC insertion in general paediatric patients. Study design: Cochrane methodology to systematically search for randomised controlled trials comparing landmark to ultrasound‐guided PIVC insertion. Data sources: Cochrane Central Register of Controlled Trials, US National Library of Medicine, Cumulative Index to Nursing and Allied Health, Embase. Data extraction: English‐language, paediatric trials published after 2000, reporting first‐attempt insertion success, overall PIVC insertion success, and/or time to insert were included. Central venous, non‐venous and trials including only difficult intravenous access were excluded. Data were independently extracted and critiqued for quality using GRADE by three authors, and analysed using random effects, with results expressed as risk ratios (RR), mean differences (MD) and 95% confidence intervals (CI). Registration (CRD42020175314). Results: Of 70 titles identified, 5 studies (995 patients; 949 PIVCs) were included. There was no evidence of an effect of ultrasound guidance, compared to landmark, for first‐attempt insertion success (RR 1.27; 95% CI 0.90–1.78; I 2  = 88%; moderate quality evidence), overall insertion success (RR 1.14; 95% CI 0.90–1.44; I 2  = 82%; low quality evidence), or time to insertion (mean difference −3.03 min; 95% CI −12.73 to 6.67; I 2  = 92%; low quality evidence). Limitations: Small sample sizes, inconsistent outcomes and definitions in primary studies precluded definitive conclusions. Conclusions: Large clinical trials are needed to explore the effectiveness of ultrasound guidance for PIVC insertion in paediatrics. Specifically, children with difficult intravenous access might benefit most from this technology.